Understanding causes of and developing effective interventions for schizophrenia and other psychoses - Jesus Perez; Debra A Russo; Jan Stochl; Gillian F Shelley; Carolyn M Crane; Michelle Painter; James B Kirkbride; Tim J Croudace; Peter B Jones (NIHR Journals Library, 2016)
Background: Early-intervention services (EISs) offer prompt and effective care to individuals with first-episode psychosis (FEP) and detect people at high risk (HR) of developing it. Aims: We aimed to educate general practitioners about psychosis and guide their referrals to specialist care; investigate determinants of the transition of HR to FEP; and predict numbers of new cases to guide policy and service planning. Incidence of psychosis in socially and ethnically diverse settings: We studied the incidence of new referrals for psychosis in a well-established EIS called CAMEO [see www.cameo.nhs.uk (accessed 18 January 2016)] and built on other epidemiological studies. The overall incidence of FEP was 45.1 per 100,000 person-years [95% confidence interval (CI) 40.8 to 49.9 per 100,000 person-years]. This was two to three times higher than the incidence predicated by the UK Department of Health. We found considerable psychosis morbidity in diverse, rural communities. Development of a population-level prediction tool for the incidence of FEP: We developed and validated a population-level prediction tool, PsyMaptic, capable of accurately estimating the expected incidence of psychosis [see www.psymaptic.org/ (accessed 18 January 2016)]. The Liaison with Education and General practiceS (LEGS) trial to detect HR: We tested a theory-based intervention to improve detection and referral of HR individuals in a cluster randomised controlled trial involving primary care practices in Cambridgeshire and Peterborough. Consenting practices were randomly allocated to (1) low-intensity liaison with secondary care, a postal campaign to help with the identification and referral of individuals with early signs of psychosis, or (2) the high-intensity theory-based intervention, which, in addition to the postal campaign, included a specialist mental health professional to liaise with each practice. Practices that did not consent to be randomised included a practice-as-usual (PAU) group. The approaches were implemented over 2 years for each practice between April 2010 and October 2013. New referrals were stratified into those who met criteria for HR/FEP (together: psychosis true positives) and those who did not fulfil such criteria (false positives). The primary outcome was the number of HR referrals per practice. Referrals from PAU practices were also analysed. We quantified the cost-effectiveness of the interventions and PAU using the incremental cost per additional true positive identified. Of 104 eligible practices, 54 consented to be randomised. Twenty-eight practices were randomised to low-intensity liaison and 26 practices were randomised to the high-intensity intervention. Two high-intensity practices withdrew. High-intensity practices referred more HR [incidence rate ratio (IRR) 2.2, 95% CI 0.9 to 5.1; p = 0.08], FEP (IRR 1.9, 95% CI 1.05 to 3.4; p = 0.04) and true-positive (IRR 2.0, 95% CI 1.1 to 3.6; p = 0.02) cases. High-intensity practices also referred more false-positive cases (IRR 2.6, 95% CI 1.3 to 5.0; p = 0.005); most (68%) of these were referred on to appropriate services. The total costs per true-positive referral in high-intensity practices were lower than those in low-intensity or PAU practices. Increasing the resources aimed at managing the primary-secondary care interface provided clinical and economic value. The Prospective Analysis of At-risk mental states and Transitions into psycHosis (PAATH) study: We aimed to identify the proportion of individuals at HR who make the transition into FEP and to elucidate the common characteristics that can help identify them. Sixty help-seeking HR individuals aged 16-35 years were stratified into those who met the criteria for HR/FEP (true positives) according to the Comprehensive Assessment of At-Risk Mental States (CAARMS) and those who did not (false positives). HR participants were followed up over 2 years using a comprehensive interview schedule. A random sample of 60 healthy volunteers (HVs) matched for age (16-35 years), sex and geographical area underwent the same battery of questionnaires. Only 5% of our HR sample transitioned to a structured clinical diagnosis of psychosis over 2 years. HR individuals had a higher prevalence of moderate or severe depression, anxiety and suicidality than HVs. In fact, psychometric analyses in other population samples indicate that psychotic experiences measure the severe end of a common mental distress factor, consistent with these results. HR individuals also experienced significantly more traumatic events than HVs, but equivalent distress. Almost half of HR individuals had at least one Schneiderian first-rank symptom traditionally considered indicative of schizophrenia and 21.6% had more than one. HR individuals had very poor global functioning and low quality of life. Conclusions: This National Institute for Health Research programme developed our understanding of the social epidemiology of psychosis. A new theory-based intervention doubled the identification of HR and FEP in primary care and was cost-effective. The HR mental state has much in common with depression and anxiety; very few people transitioned to full psychosis over 2 years, in line with other recent evidence. This new understanding will help people at HR receive appropriate services focused on their current mental state. Trial registration: The primary LEGS trial is registered as ISRCTN70185866 and UKCRN ID 7036. The PAATH study is registered as UKCRN ID 7798. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.